A Prospective Single-blind Randomized Controlled Trial of Chewing Gum on Bowel Function Recovery After Posterior Spinal Fusion Surgery for Adolescent Idiopathic Scoliosis. Issue 3 (April 2018) - Meng, Yichen; Lin, Tao; Shao, Wei; Jiang, Heng; Li, Tangbo; Gao, Rui; Zhou, Xuhui
Abstract : Purpose: To evaluate the effectiveness of chewing gum on promoting bowel function recovery in adolescent idiopathic scoliosis patients undergoing surgical correction. Materials and Methods: Adolescent idiopathic scoliosis patients scheduled for posterior spinal fusion surgery at our institution were randomized to either group 1 (chewing gum) or group 2 (control). The primary endpoints were time to flatus, time to bowel movement, length of hospital stay, and time to liquid or solid. The secondary endpoints were postoperative opioid consumption, incidence of complications, pain scores, and nausea scores. In addition, a meta-analysis of available data from the literature was performed identifying 2 studies with quantitative data on the efficacy of gum chewing after scoliosis correction surgery. Results: In total, 125 patients (63 gum; 62 control) were included in our analysis after randomization. There was no significant difference in time to first flatus ( P =0.087), time to bowel movement ( P =0.307), time to liquid or solid, length of postoperative hospital stay ( P =0.954), postoperative complications, opioid consumption, and postoperative nausea scores between the 2 groups. The postoperative pain scores on postoperative day 1 were significantly lower ( P =0.027). There was a significant decrease in the time to the first flatus for patients having selective thoracic fusion in both groups than those having fusion to lumbar spine. Meta-analysis also indicated there was no significant difference in outcomes of bowel function between the 2 groups. Conclusions: Our institutional data and meta-analysis collaboratively suggested that chewing gum did not hasten the return of bowel function.